KAJIAN PENGEMBANGAN POTENSI UPACARA ADAT HUS SEBAGAI ATRAKSI WISATA BUDAYA DI PULAU ROTE, NUSA TENGGARA TIMUR - , Dorce Juliance Mandala; , Prof. Dr. Heddy Shri Ahimsa-Putra, MA, M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Development in social life of Rote Island resulted in the marginalization of some cultural heritages such as rites and traditional ceremonies. Hus traditional ceremony is one of the cultural heritages that begin to extinct. It causes the young generations of Rotenese to have little knowledge of their culture. Therefore, a research toward the potency development of Hus traditional ceremony as a cultural tourism attraction is needed to introduce a cultural attraction in Rote Island, beside its recognized beach and maritime tourism. The objectives of this research were to find out about Hus traditional ceremony and its procession, to identify its potencies as a cultural tourism attraction, and to formulate strategies to develop it. The method used in this research was descriptive method with qualitative approach where the data were taken used the library research, observation, and interview method toward those whom took part directly or indirectly in the event and in the development of it. The acquired data were analized continuously and were developed during the research process. The process of data analyzing covered data reduction (data simplification), classification, and verification to draw conclusions. The result of the research showed that Hus traditional ceremony was a social festival of decorated horsesâs parade, horse skills races, and eating and dancing together. The potencies of Hus traditional ceremony based on four variabels were as follows. Uniqueness: horse parade, shouting/eki, the traditional tiâilangga hat, the traditional dances such as kakamusu, foti, and kebalai, traditional music instrument sasando, and its races. Aesthetics side: outfit of the horsemen and the dancers, the decorated horses. Religious side: its function as a thanksgiving festival. Scientific side: in its timing of festival. In its whole procession, there were some found problems such as the timing, the access, the location, the attractionâs management, the promotion, and the lack of peopleâs participation. Therefore, strategies that could be implemented were to preserve and to develop Hus attractions